The fractured Moon: Production and saturation of porosity in the lunar highlands from impact cratering - Soderblom, J.; Evans, A.; Johnson, B.; Melosh, H.; Miljkovic, Katarina; Phillips, R.; Andrews-Hanna, J.; Bierson, C.; Head, J.; Milbury, C.; Neumann, G.; Nimmo, F.; et al. (Blackwell Publishing Ltd, 2015)
©2015. American Geophysical Union. All Rights Reserved. We have analyzed the Bouguer anomaly (BA) of ~1200 complex craters in the lunar highlands from Gravity Recovery and Interior Laboratory observations. The BA of these craters is generally negative, though positive BA values are observed, particularly for smaller craters. Crater BA values scale inversely with crater diameter, quantifying how larger impacts produce more extensive fracturing and dilatant bulking. The Bouguer anomaly of craters larger than 93-19+47 km in diameter is independent of crater size, indicating that there is a limiting depth to impact-generated porosity, presumably from pore collapse associated with either overburden pressure or viscous flow. Impact-generated porosity of the bulk lunar crust is likely in a state of equilibrium for craters smaller than ~30 km in diameter, consistent with an ~8 km thick lunar megaregolith, whereas the gravity signature of larger craters is still preserved and provides new insight into the cratering record of even the oldest lunar surfaces.